Pengaruh Penggunaan Ankle Foot Orthose (AFO) dan Backslab terhadap Kualitas Hidup pada Pasien Cerebral Palsy - Prasetyo Catur Utomo; S.Th Susilowati; Retno Azizah (Politeknik Kesehatan Tanjung Karang, 2017)
This study was conducted using cross sectional method with two groups, post-only design. Subjects were 15 children with Cerebral Palsy who was using AFO and Backslab, 15 Cerebral Palsy children were only doing Physiotherapy Treatment, this kind of research was two unpaired groups. It was done in Points Neurodevelopmental Clinic Pediatric & Therapy Center (PNTC) Surakarta, January to March 2016. Group AFO and Backslab were given quality questionnaire of life, group Physiotherapy Treatment were also given quality questionnaire of life. Quality of life questionnaire composed of six domains and 36 questions. Data analized by Independent Samples T Test. Each group tested for normality using the Shapiro-Wilk, a group that uses AFO and Backslab and also the ones who just do Physiotherapy Treatment has a value of p = 0.408 and p = 0.168. The results of the two groups showed normal distribution of data, because it has a value of p> 0.05. Test the hypothesis using independent sample t test with a result of which the value of p = 0.000, p <0.05, it means that there was the effect of the AFO and Backslab on the quality of life in patients with cerebral palsy. It can be concluded that use of AFO and Backslab influenced significantly to the quality of life in patients with Cerebral Palsy.